Empirical Analysis of Strategic Management Failures:The Case Study of SME in China - Xie, Dan (2012)
In China, the small and medium enterprises (SME) of registered in the Industry and Commercial Bureau have more than 10 million, and there is more than 99% of the total number of registered enterprises. SMEs are important force of the national economy that they are play the role as the root of the green development of national economy. In order to make SMEs to adapt to the needs of economic development and market competition, it is necessary to builds clear strategic goals and strategic direction of the development. Similarly in terms of, the enterprises will hard to survival if the strategy without right strategy for guiding the development of enterprises. Moreover, due to the increasing of competition, the SME strategy has been widespread concern by the enterprises. However, enterprises are also made many mistakes on their strategy design and implementation, and these mistakes cause the strategic failures. The analysis of this paper work is focus on the strategic failure by an empirical case study. It consists of the current situation and external limitations of the SMEs, the major strategic failures of SMEs, the solutions of these failures.